NANODIAMOND SYNTHESIS AND CHARACTERIZATION, AS WELL AS ITS USE AS AN ANTI-POLISHING AGENT ON SIO2 SUBSTRATE - Durlab Das, S.Venkatesan, KARTHIK A (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Nanodiamond particles were produced, purified, and described in the current work. The surface of the nanodiamond was then oxidised to create a uniform coating of COOH groups. Finally, the functionalized particles were placed on the SiO2 substrate and their anti-polishing properties were studied. FT-TR, TGA, TEM, and SEM were used to characterise the products of this study